PENGARUH KECERDASAN INTELEKTUAL DAN KECERDASAN EMOSIONAL DALAM RANGKA OPTIMALISASI KINERJA SUMBER DAYA MANUSIA DI BANDAR UDARA SULTAN MUHAMMAD SALAHUDDIN BIMA - Faturrahman; Fryda Fatmayati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Intellectual intelligence is a very basic thing that must be possessed by every human resource in providing services. But intellectual intelligence alone is not enough to support the quality of services provided by human resources. Therefore, emotional intelligence is also needed from the human resources themselves in providing services. This study uses quantitative methods to test hypotheses, describe reality, show relationships between factors, provide factual descriptions, measure and anticipate results. Quantitative research designs must first be structured, standardized, formalized, and designed as comprehensively as possible. From the F test analysis it is known that post-Covid-19 HR performance at Sultan Muhammad Salahuddin Bima Airport is influenced by intellectual intelligence and emotional intelligence. of these three variables has a determination of 78.2% and the rest of the variables are influenced by other factors not examined in this study. After the Covid-19 pandemic at Sultan Muhammad Salahuddin Bima airport, the performance of human resources was influenced by intellectual intelligence and emotional intelligence. Besides that intellectual intelligence and emotional intelligence simultaneously influence the performance of human resources.